A Literature Review on Reconstructing Islamic Educational Philosophy in the Digital Age: Between Classical Wisdom and AI Ethics - Evi juliyanti; Iskandar Iskandar; Latifur Rahmi; Fatimah Zohra (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The development of digital technology and Artificial Intelligence (AI) presents epistemic, ethical, and ontological challenges that require a reconstruction of the philosophy of Islamic education to remain relevant in the era of disruption and digital posthumanism. The growing integration of AI into learning processes, knowledge production, and educational decision-making reshapes understandings of humanity, knowledge, and values. This conceptual study aims to reformulate the ontological, epistemological, and axiological foundations of Islamic education in response to intelligent technologies. This study employs a critical literature review of scholarly works published between 2020 and 2025 on the philosophy of Islamic education, technology ethics, and contemporary AI discourse, drawing from both Western perspectives and classical as well as modern Islamic thought. The findings indicate that, ontologically, Islamic education views human beings as moral subjects and khalifah endowed with spiritual dimensions and transcendent responsibility, rendering them irreducible to algorithmic entities or computational systems. Epistemologically, AI is positioned as an assistive epistemic tool that supports knowledge acquisition and management, rather than replacing human reason or divine revelation. Axiologically, maqāṣid al-sharī‘ah provide an ethical framework to ensure that the use of AI aligns with principles of justice, public benefit (maṣlaḥah), responsibility, and human fitrah. This study proposes a Digital-Humanistic Philosophy of Islamic Education that integrates classical Islamic wisdom with contemporary AI ethics, affirms the primacy of values over technology, positions technology as a servant of values, and centers human beings as the core of education and moral responsibility in the digital age.